PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KARAKTER PADA MATERI NILAI-NILAI PANCASILA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS 4 SEKOLAH DASAR - Giri, Grace Maria; Anwar, Moh. Farid Nurul; Chotimah, Chusnul; M. Rifa'i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a character-based picture storybook on the topic of Pancasila values as a learning medium for fourth-grade Pancasila Education in elementary school.The background of this research is the limited use of contextual and innovative learning media, which causes the delivery of Pancasila values to be predominantly verbal and abstract. As a result, students tend to be less active and experience difficulties in understanding and internalizing Pancasila values in their daily lives. The method used in this study was Research and Development (R&D) based on a simplified Borg & Gall model. The research stages included data collection, planning, initial product development, expert validation, revision, small-scale trials, large-scale trials, and the production of the final product. Data collection instruments consisted of questionnaires and observation sheets used during the validation and trial processes. The validation results showed that the media obtained a score of 92 from the material expert, 96 from the media expert, and 86 from the language expert. The trial involving 14 students resulted in a total score of 1,220, with a success percentage of 87.14%, which was categorized as very effective in supporting the learning process. Therefore, the developed media is considered valid and effective for use as an instructional tool. It is feasible to be implemented as an alternative learning medium for fourth-grade Pancasila Education in elementary schools.